A comparative settlement prediction of limestone blended materials using Asaoka and hyperbolic method - Uy, Erica Elice S. (Animo Repository, 2018)
The construction industry in the Philippines is predicted to sustain its growth up to 2021 because of the infrastructure plan of the government according to the Philippine Infrastructure Report. With this, the demand for construction materials would increase and as a result, an increase in prices is expected. To address this problem, an alternative material must be explored. A promising material is a limestone because it is abundant in the Philippines. These materials can be used as a material for structural fill or embankment. In order to determine the material's possible use its capacity to withstand loads must be checked. In this study, its compressibility is the main focus. Its consolidation parameters were first obtained by performing one-dimensional consolidation test. Limestone wastes were mixed with a conventional soil and it is proportioned at 0%, 20%, 40%, 60% and 100%. After the consolidation parameters were determined, the data from the consolidation test were used to predicting the settlement behavior of the material. The Asaoka method and hyperbolic method were used in the prediction and the results of both methods were compared. Based on the results, it was observed in the one-dimensional consolidation test, the limestone waste used had a minimal effect on the compressibility of the conventional material used. Lastly, the prediction of the hyperbolic method is larger for some mix proportions.